Additive manufacturing of hydroxyapatite bone scaffolds via digital light processing and in vitro compatibility. Issue 8 (1st June 2019) - Liu, Zibo; Liang, Huixin; Shi, Tianshu; Xie, Deqiao; Chen, Ruoyu; Han, Xiao; Shen, Lida; Wang, Changjiang; Tian, Zongjun
Abstract: The bioceramic material hydroxyapatite (HA) is widely used in the field of bone repair. Based on additive manufacturing (AM) techniques, HA is fabricated with complex geometry to satisfy biomedical application requirements. Digital light processing (DLP) is a promising AM technique that is capable of producing HA parts with high accuracy and efficiency. The fabrication of HA parts using DLP is investigated in this study. Properties of the HA ceramic slurry and the process parameters of curing, debinding, and sintering are initially examined. The mechanical properties, porosity, and shrinkage of the sintered samples is then investigated. The experimental results show that ceramic samples with density above 90%, microhardness up to 270 HV, and flexural strength of 41.3 MPa can be manufactured using the DLP method. Hydroxyapatite bone scaffolds are then prepared with pore sizes of 300–600 μm, porosity of about 49.8%, and compressive strength of 15.25 MPa, and the scaffolds are cultured with osteoblast precursor cells to detect biocompatibility. Results illustrate that the produced scaffolds possess strong biocompatibility and can promote osteoblast proliferation, adhesion, and differentiation. The HA bone scaffolds fabricated by DLP AM show strong potential to fulfill a constructive role in the medical field of human bone repair.